Intelligent automation and systems engineering - Ao, Sio-Iong.; Amouzegar,Mahyar; Rieger,Burghard B.; SpringerLink (Online service). (New York Springer, 2011)
Intelligent systems are required to facilitate the use of information provided by the internet and other computer based technologies. This book describes the state-of-the-art in Intelligent Automation and Systems Engineering. Topics covered include Intelligent decision making, Automation, Robotics, Expert systems, Fuzzy systems, Knowledge-based systems, Knowledge extraction, Large database management, Data analysis tools, Computational biology, Optimization algorithms, Experimental designs, Complex system identification, Computational modeling, Systems simulation, Decision modeling, and industrial applications. Provides a comprehensive reference on Intelligent Automation and Systems Engineering; Covers fundamental issues, new technologies and applications; Describes methods for modeling, where the information available may be imprecise, uncertain, incomplete or of a linguistic nature.
Evidence Fusion for Real Time Click Fraud Detection and Prevention -- Biped Locomotion with Arm Swing, Based on Truncated Fourier Series and Bees Algorithm Optimizer -- Bio-inspired Pneumatic Muscle Actuated Robotic System -- Evaluation of an Orthopedic Surgical Robotic System Orthoroby on Bone Cadaver -- Natural Intelligence Based Automatic Knowledge Discovery for Medical Practitioners -- Design and Optimal Control of a Linear Electromechanical Actuator for Motion Platforms -- Design and Optimal Control of a Linear Electromechanical Actuator for Motion Platforms with Six Degrees of Freedom -- Parametric Identification of a Power-system Emulator -- Enhanced Adaptive Controller Applied to SMA Wire Control -- A Standalone System to Train and Evaluate Operators of Power Plants -- Lube Oil Systems Models for Real Time Executions Used on a Training Power Plant Simulator -- Stochastic Analysis and Particle Filtering of the Volatility -- Numerical Simulation of Finite Slider Bearings Using Control Volume Method -- Automated Production Planning and Scheduling System for Composite Component Manufacture -- Assessment Scenarios of Virtual Prototypes of Mining Machines -- A Framework for the Selection of Logistic Service Provider Using Fuzzy Delphi and Fuzzy TOPSIS -- Bee Algorithm for Solving Yield Optimization Problem for Hard Disk Drive Component and Supplier's Rating Constraints and Heuristic Performance Comparison -- Integrated Modelling of Functions and Requirements in Product Design and Factory Planning -- Towards a Strategy to Fight the Computer Science (CS) Declining Phenomenon -- Development of Power Plant Simulators and their Application in an Operations Training Center -- Benefits of Unstructured Data for Industrial Quality Analysis -- Evaluation: The Objectivity Measurement of Frequent Patterns -- Change-point Detection Based on SSA in Precipitation Times Series -- Non-linear Image Recovery from a Single Frame Super Resolution Using Pearson Type VII Density -- Research on the Building Method of Domain Lexicon Combining Association Rules and Improved TF*IDF -- Combining Multi-scale and Multidirectional Analysis for Edge Detection Using a Statistical Thresholding -- Soft Vector Quantization with Inverse Power-functions for Machine Learning Applications -- ANFIS-based P300 Detection Using Wavelet Feature Extraction on Blind Source Separated EEG Signals -- A Hyperbola-pair Based Road Detection System for Autonomous Vehicles -- Application of the Real-time Concurrent Constraint Calculus -- Teaching and Learning Routing Protocols Using Visual Educational Tools: The Case of EIGRP -- Relevance Features Selection for Intrusion Detection -- A Visual Application for Teaching and Learning the Advanced Concepts of the Diffusing Update Algorithm for EIGRP.
Electronic reproduction.
Keywords: Electronic books; Intelligent control systems; Automation